The Association between Occupational Burnout and Spiritual Wellbeing in Emergency Nurses: A Cross-Sectional Study - Hedayat Jafari; Rahmatollah Marzband; Mahsa Kamali; Mahmood Moosazadeh; Pooyan Ghorbani Vajargah; Samad Karkhah; Joseph Osuji; Behzad Davaribina (Bulletin of Emergency and Trauma, 2023)
Objective: This study evaluated the occupational burnout (OB) and spiritual well-being (SWB) of emergencynurses as well as the associations between these variables.Method: This cross-sectional study was conducted in six hospitals and emergency medical centers affiliated withArdebil University of Medical Sciences (Ardebil, Iran), in 2020. Data were collected via socio-demographic,Spiritual Well-Being Scale (SWBS), and Maslach Burnout Inventory (MBI) questionnaires.Results: This study included 239 emergency department nurses. The mean age of the participants was 34.4±6.4years. The mean of existential well-being and religious well-being was 40.3±8.7 and 41.0±9.2, respectively. Theresults indicated that moderate (P=0.007) and severe (P<0.001) personal accomplishment was a positive andsignificant predictor of the SWB in emergency department nurses.Conclusion: Proper planning and provision of suitable educational programs in the dimension of the SWBof nurses prevent the creation and continuation of OB and increase the self-efficacy and job satisfaction ofemergency medical staff, resulting in better patient care.